Spatial Barriers and the Tendency of the Utilization of Mediated Citizenship by Villagers in Accessing Public Services - Hidayat, Rahmad; Akhyar, Akhyar; Sauki, Muhammad (ijd-demos, 2021)
AbstractThis paper aims to discuss the dynamic intersection between the spatial barriers and the tendency of the utilization of "mediated citizenship" by villagers in accessing public services. It is important to map out how villagers interact with authoritative service providers at the local government level, which is not done directly, but through the mediation of a third party, namely a local NGO that is implementing a program in their village. Based on the context of Oi Bura Village, the tendency of the utilization of mediator services ofÂ  "LAKPESDAM PCNU Kabupaten Bima" in accessing public services (especially the residential identities) began to take shape because it was triggered by the poor people's consideration about the spatial stretch of their village area with the site of the service provider that would have an impact on financial expenses and bureaucratic severity factors that must be passed when accessing these basic services. Although the residential identities should be obtained automatically based on formal status as an Indonesian citizen, in practice the access of the poor villagers to basic services is achieved through a third party mediation role. The limitations of the service providers' responsiveness, accountability and institutional capacity to act proactively in solving the public problems are increasingly opening up the chance for "permanence" of facilitation of the state-citizen interaction by third parties.Keywords:Â access, citizenship, mediator, service, spaceÂ Â AbstrakMakalah ini bertujuan untuk membahas persimpangan dinamis antara hambatan spasial dan kecenderungan pemanfaatan "mediated citizenhip" oleh warga desa dalam mengakses layanan publik. Penting untuk memetakan bagaimana masyarakat desa berinteraksi dengan pemberi layanan otoritatif di tingkat pemerintah daerah, yang tidak dilakukan secara langsung, melainkan melalui mediasi pihak ketiga, yaitu LSM lokal yang melaksanakan program di desanya. Berdasarkan konteks Desa Oi Bura, kecenderungan pemanfaatan jasa mediator â€œLAKPESDAM PCNU Kabupaten Bimaâ€ dalam mengakses pelayanan publik (khususnya identitas permukiman) mulai terbentuk karena dipicu oleh pertimbangan masyarakat miskin terhadap tata ruang. hamparan wilayah desanya dengan lokasi penyedia layanan yang tentunya berdampak pada pengeluaran keuangan dan faktor keparahan birokrasi yang harus dilalui saat mengakses layanan dasar tersebut. Meskipun identitas kependudukan seharusnya diperoleh secara otomatis berdasarkan status formal sebagai warga negara Indonesia, pada praktiknya akses masyarakat miskin terhadap layanan dasar dicapai melalui peran mediasi pihak ketiga. Keterbatasan daya tanggap, akuntabilitas, dan kapasitas kelembagaan penyedia layanan untuk bertindak proaktif dalam menyelesaikan masalah publik semakin membuka peluang untuk "kelanggengan" fasilitasi interaksi negara-warga oleh pihak ketiga.Kata kunci: akses, citizenship, mediator, layanan, ruang.